Rebuilding strength: surgical intervention and rehabilitation for bilateral spontaneous quadriceps tendon rupture—a case report - Dong, Huaize; Yang, Jin; Yu, Hao; Zhu, Jinsong; Yang, Jibin (Frontiers in Surgery, 2024)
The quadriceps tendon, crucial for body movement, is among the body's strongest tendons.Factors like diabetes or hormone use can weaken it, making even minor trauma potentially causing rupture. Bilateral spontaneous quadriceps tendon rupture, where both tendons tear simultaneously, is rare. Prompt diagnosis and treatment are crucial. We present a case of a 44-year-old woman who experienced bilateral rupture after falling while doing chores. She had immediate pain and limited knee movement. Diagnosis via physical examination and CT/MRI scans confirmed the rupture. Surgical repair followed by rehabilitation led to significant pain reduction and improved function within two months. Overall, her postoperative outcome was satisfactory. This study underscores the importance of clear diagnosis, timely surgery, and thorough rehabilitation for optimal patient recovery from bilateral quadriceps tendon rupture.